An Insight into nd10 Metal Cyanide‐based Coordination Polymers Through ab‐initio Calculations: Electronic Properties and Optical Response. Issue 7 (5th January 2023) - Mojica, Rodrigo; Torres, Ana E.; Avila, Yosuan; Reguera, Edilso
Abstract: Semiconductors are essential for modern life since they are the basis of many current technologies that are related to better living standards. Some of them, characterized by the periodic assembling of metal cyanides with filled d‐shell (nd 10 ) constitute an interesting series of cyanide‐based coordination polymers with physical properties such like anomalous anisotropic thermal expansion and quantum confinement effects related to the polymer's width that can be exploited for technological applications. Herein, the electronic structure of nd 10 metal cyanide‐based systems were studied both experimentally and through Density Functional Theory. The band gap found for one‐dimensional (1D) −M−C≡N− (M=Cu, Ag, Au) and tetrahedral M−(C≡N)2 (M=Zn, Cd, Hg) systems can be attributed to Laporte‐allowed π → → π* (Metal to Ligand Charge Transfer mechanism) combined with metal center (d → → s, p) electronic transitions. Aurophilic bonding was found on the AuCN structure, and a new forbidden electronic transition associated to its band gap is reported. Computed effective and reduced masses from carriers revealed that carrier mobility and quantum confinement effects are greater in 1D systems. Abstract : Bonding interaction in nd 10 metal cyanides and nature of their electronic structure and related optical properties are investigated in this research article.